PHYSICO-MECHANICAL PROPERTIES OF THAILAND AND YELLOW BAMBOO PLANTED IN LAGUNA AND BENGUET, PHILIPPINES - Oliver S. Marasigan; Mario Angelo M. Mundin; Shereyl A. Daguinod; Jayric F. Villareal (BIOTROPIA, 2026)
ARTICLE HIGLIGHTS- Thailand bamboo showed higher density and strength for structural use- Yellow bamboo suited for composites, crafts, and fiber boards- Species, site, and culm height influence bamboo performanceABSTRACTBamboo is gaining recognition as a sustainable construction material, but data on the physico-mechanical properties of species grown in the Philippines remain limited. This study assessed Thailand bamboo (Thyrsostachys siamensis Gamble) and yellow bamboo (Bambusa vulgaris Schrad. ex J.C. Wendl.) planted in Laguna and Benguet. Tests were conducted following ASTM D143 (2019) and ISO 22157 (2019) standards, focusing on moisture content (MC), basic relative density (RD), shrinkage, static bending, compression (CPG), and shear strength parallel to the grain (SS). Significant interspecies differences were observed. Yellow bamboo exhibited higher MC (34%), radial (32%), tangential (92%), and volumetric shrinkage (53%), while Thailand bamboo had 29% higher RD, indicating better mechanical performance. Location influenced several properties, i.e., yellow bamboo from Laguna showed 46% higher MC, while Benguet samples showed higher modulus of elasticity and stress at the proportional limit. Thailand bamboo from Laguna had a 7% higher modulus of rupture, while yellow bamboo from Benguet showed 42% increase compared to Laguna. Thailand bamboo from Benguet showed higher CPG and SS, though yellow bamboo from Laguna outperformed in these properties. Axial position affected MC, shrinkage, CPG, and SS, but node presence did not influence CPG and SS. The higher density and strength of Thailand bamboo make it ideal for structural applications, whereas the larger culm and softer fibers of yellow bamboo are ideal for handicrafts, composites boards, and bioenergy.